IT Challenges in Designing and Implementing Online Natural History Collection Systems - Marcin Lawenda; Paweł Wolniewicz (Diversity)
Numerous institutions engaged in the management of Natural History Collections (NHC) are embracing the opportunity to digitise their holdings. The primary objective is to enhance the accessibility of specimens for interested individuals and to integrate them into the global community by contributing to an international specimen database. This initiative demands a comprehensive digitisation process and the development of an IT infrastructure that adheres to stringent functionality, reliability, and security standards. This endeavour focuses on the procedural and operational dimensions associated with accurately storing and managing taxonomic, biogeographic, and ecological data about biological specimens digitised within a conventional NHC framework. The authors suggest categorising the IT challenges into four distinct areas: requirements, digitisation, design, and technology. Each category discusses several selected topics, highlighting often underestimated essentials for implementing the NHC system. The presented analysis is supported by numerous examples of specific implementations, enabling a better understanding of the given topic. This document serves as a resource for teams developing their systems for online collections, offering post factum insights derived from implementation experiences.